Transgenic herbicide resistance in plants - Rao, V. S. (Vallurupalli Sivaji), 1940- (CRC Press, 2015)
This book provides a comprehensive and in-depth discussion on the development of herbicide resistance during the past 50 years, emphasizing the biochemical pathways of herbicide resistance in weeds. It discusses the principles of plant genetics, different methods of genetic engineering, makingof transgenic plants, various transgenic crops conferred with herbicide resistance, evolution of weed, problems subsequent to growing of transgenic crops, benefits and risks of growing transgenic crops, and management of transgenic crops. Packed with up-to-date information, the book includes relevant refe.